2018
DOI: 10.1002/hbm.24395
|View full text |Cite
|
Sign up to set email alerts
|

From eyes‐closed to eyes‐open: Role of cholinergic projections in EC‐to‐EO alpha reactivity revealed by combining EEG and MRI

Abstract: Alpha rhythm (8 to 12 Hz) observed in EEG over human posterior cortex is prominent during eyes‐closed (EC) resting and attenuates during eyes‐open (EO) resting. Research shows that the degree of EC‐to‐EO alpha blocking or alpha desynchronization, termed alpha reactivity here, is a neural marker of cognitive health. We tested the role of acetylcholine in EC‐to‐EO alpha reactivity by applying a multimodal neuroimaging approach to a cohort of young adults and a cohort of older adults. In the young cohort, simulta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
66
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 81 publications
(82 citation statements)
references
References 85 publications
11
66
0
Order By: Relevance
“…EEG data from three occipital electrodes (O1, O2, and Oz) were selected for the alpha reactivity analysis ( Fig. 2a) [17]. For each electrode separately, the power spectral density (PSD) was estimated using Bartlett's method with a frequency resolution of 0.25 Hz and a Hamming window.…”
Section: Alpha Reactivity Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…EEG data from three occipital electrodes (O1, O2, and Oz) were selected for the alpha reactivity analysis ( Fig. 2a) [17]. For each electrode separately, the power spectral density (PSD) was estimated using Bartlett's method with a frequency resolution of 0.25 Hz and a Hamming window.…”
Section: Alpha Reactivity Analysismentioning
confidence: 99%
“…The resulting PSD for the three electrodes was averaged across the 45 epochs and across the three electrodes for each condition separately (eyes open and eyes closed). Alpha reactivity was then calculated according to the following formula [17]: where alpha power was computed as the relative power within a frequency bin around the individual alpha peak frequency ± 2 Hz. Individual alpha peak frequencies were calculated by finding the peak in the PSD in the extended alpha frequency band from 4 to 14 Hz [20] using the eyes-closed data.…”
Section: Alpha Reactivity Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…10 In addition to resting state fMRI-based evidences, electroencephalography (EEG)-based and magnetoencephalography (MEG)-based methods also found different brain network topology between EO/EC, indicating that the characteristic brain active patterns might have physiological meanings. [11][12][13] The above findings suggested that the internetwork neural mechanisms might be distinctive between EO/EC. Therefore, resting state network measures could be potential neuroimaging-markers for discriminative analysis of EO/EC using machine learning.…”
Section: Introductionmentioning
confidence: 75%
“…The GABA and glutamate systems, the primary inhibitory and excitatory transmitters in the brain, have been shown to be altered in MDD (Godfrey et al, 2018;Voineskos et al, 2019). As well as this, neuromodulators such as serotonin and dopamine, which influence neural excitability, are known to be affected in MDD (Belujon and Grace, 2017;Morrissette and Stahl, 2014) and to play a role in cortical activity changes between EC and EO conditions (Wan et al, 2019). It thus seems possible that the reported changes in cortical dynamic reactivity are related to changes in these systems (Hu et al, 2019;Ramirez-Mahaluf et al, 2017;Wiebking et al, 2014).…”
Section: Discussionmentioning
confidence: 99%